Excellence Management at Princess Nourah Bint Abdul Rahman University and Ways to Develop it according to the European Model of Excellence (EFQM) - Alshammari, Adel Ayed; Alghamdi, Mashael Ali (Dirasat: Educational Sciences, 2020)
The study aims to identify the reality of excellence management at Princess Nourah Bint Abdul Rahman University and ways to develop it according to the EFQM European Model of Excellence, from the point of view of the university’s academic leaders. A descriptive approach was adopted with its survey and analytical inputs. Its data was collected through a questionnaire specially designed for it, and distributed to a sample of (56) individuals. The study concluded that the degree of availability of management excellence at the university for all dimensions came to a medium degree, and the highest was the availability of the leadership dimension, while the lowest was the human resources dimension. The study recommends a set of recommendations, most notably working on spreading the culture of excellence and applying its models at Princess Nourah Bint Abdul Rahman University and in higher education institutions, benefiting from global experiences and expertise in this field, and establishing specialized units to foster excellence at universities.